FRI0489 The Number of Micro-Hemorrhages and Micro-Thrombosis Detected by Nailfold Videocapillaroscopy is Predictive of Disease Activity in Patients with Systemic Sclerosis. (10th June 2014) - Sambataro, D.; Sambataro, G.; Vitali, C.; Maglione, W.; Zaccara, E.; Di Luca, G.; Polosa, R.; Afeltra, A.; Del Papa, N.
Abstract : Background: As in other autoimmune diseases, even in systemic sclerosis (SSc) the assessment of disease activity (DA) is essential to detect the window of opportunity for a successful treatment. The so far proposed composite indexes for DA assessment imply a long and expensive patient's work up. Nailfold videocapillaroscopy (NVC) is commonly regarded as an instrument useful for SSc diagnosis and subsetting, and the presence of megacapillaries is considered the hallmark of an active disease. Objectives: Since microvascular endothelial activation represents the key mechanism of the disease progression, the present study was specifically designed to evaluate whether the presence and number of micro-hemorrhages (MH) and micro-thrombosis (MT) in NVC could be considered potential predictors of DA in SSc. Methods: The study population was constituted by 107 patients with SSc, 50 with the diffuse cutaneous (dc) and 57 with the limited cutaneous (lc) variants of the disease. European Scleroderma Study Group (ESSG) index (Valentini G, et al. Ann Rheum Dis 2001; 60:592-8)) was assumed as the gold standard for DA assessment, and patients having a score ≥3.5 classified as active. NVC was performed at the same time of DA evaluation. The sum of MH and MT detected by NVC examination in 2° to 5° fingers of both hands (named as NEMO score) was then obtained. Results: The enrolled patients were predominantly females (97/107), had a mean age of 55.8 yrs. (range 18-84 yrs.) and mean disease duration of 6.1 yrs. (range 0-30 yrs.). According with the defined cut-off value of ESSG index, 32/107 patients were active (14 with dcSSc and 18 with lcSSc). NEMO values were significantly correlated with ESSG index scores (r=0.56, p<0.0001), and with mRSS (r=0.33, p>0.001), but not with patients' age and disease duration. Considering the other components of ESSG index, NEMO score was significantly higher in patients having scleredema (p<0.0001), worsening in skin (p<0.0001), cardio-pulmonary (p<0.0005), and vascular features (p<0.002), ulcers (p<0.005), and an erythrocyte sedimentation rate ≥30 mm/h (p<0.0002). The area under the ROC curve, constructed by calculating sensitivity and specificity of different NEMO scores in correctly classifying active patients, was 0.91 (CI 0.85-0.96). The presence of at least 7 MH/MT identified the NEMO score with the highest accuracy (83.2%), and the best sensitivity/specificity balance (84.3% and 82.6% respectively). Conclusions: The presence of MH and MT appears to be a good predictor for DA in patients with SSc, and enhances the role of NVC as a quick and easy technique to select the patients potentially candidate to be more aggressively treated. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3167